Evacuation Solution for Fully Automatic Operation System of Urban Rail Transit - CHEN Xiang; LI Xiaogang; CHANG Ming; LYU Xinjun (Chengshi guidao jiaotong yanjiu)
Objective In order to ensure that FAO (fully automatic operation system) can effectively guarantee the safe evacuation of passengers in case of emergency and quickly resume operations after evacuation completion, it is proposed to study the evacuation solution for FAO system based on central remote supervision and command. Method Based on the line conditions (such as evacuation platform, trackbed, etc.) and vehicle conditions (providing side door and end door two evacuation modes) that affect the safety of passenger evacuation, and targeting the safety risks that may be encountered during the passenger evacuation process (such as passengers falling, train collision, transition switch injury, third rail electric shock, etc.), the evacuation activation, evacuation recovery, as well as the FAO multi-system linkage mechanism and protection method for coupling train evacuation are designed in detail from two different application scenarios of platform evacuation and interval evacuation. Result & Conclusion Line and vehicle conditions required for the realization of FAO system evacuation function are proposed. During the evacuation process, the central dispatcher can remotely monitor and direct the evacuation of passengers through CCTV (video surveillance system), PA (broadcast system), emergency intercom and other devices. At the same time, through the ATS (automatic train supervision) system, the central dispatcher can realize the linkage control of multiple systems, such as CC (car controller), ZC (zone controller), and CI (computer interlocking), in order to ensure the safety protection and evacuation recovery of passengers when evacuating through the side/end doors of trains with different marshalling on platforms or intervals. This solution significantly improves the safety level and efficiency of evacuation.